An analysis of the expansion of the mosque of the prophet by caliph 'Umar B. Al-KhattāB (d. 24 A.H./744 C.E.) - Omer, Spahic (Hamdard Foundation Pakistan, 2017)
This paper discusses the expansion of the Prophet’s Mosque in Madinah by Caliph ‘Umar b. al-Khattab. The paper concludes that the undertaking was in full consonance both with the spiritual benchmarks of the Islamic message and the emerging socio-cultural traditions and norms of the nascent Muslim community. So significant was the expansion and at such a critical juncture in Muslim history that it set some high standards as to the future development and nurturing of the spiritual as well as human dimensions in the sphere of Muslim architecture. The main discussion of the paper focuses on three vital dimensions of the Mosque expansion which proved significant for the early development of the authentic identity of Muslim architecture: the role of consultation and mutual agreements, which is tantamount to what is called today public participation in architecture; the significance and impact of the dynamic process of institutionalization of the Prophet’s Mosque’s myriad religious, educational, social, cultural and political activities; and the austere, yet judicious, views of ‘Umar b. al-Khattab on architecture which, by and large, reverberated the core of the Islamic attitude towards the prospect of erecting buildings. The three dimensions are dealt with after the main physical features of the Mosque expansion have been expounded. The paper also shows that so interwoven were the evolution of Muslim architectural identity and the community development processes in Islam that successfully investigating the former without systematically referring to the latter can never be complete. Thus, the orb of Muslim architecture, both as a concept and sensory reality, should always be seen as a multidimensional, universal, fluid, vibrant, expressive and as much scientific, technological and applied, as spiritual, educational and ethical, phenomenon.